Digital Transformation: The Role of Creative Economy-Based Marketing in Indonesian FnB Ramen - Selviasari, Rike; Hermawan, Agus; Ayuanti, Rafikhein Novia (PT FORMOSA CENDEKIA GLOBAL, 2024)
The application of technology, especially the internet, in the world of commerce is a common concern for both the government and society. Marketing is a fundamental problem faced by entrepreneurs. Problems in the marketing sector faced by small entrepreneurs generally focus on three things, namely market and product competition problems, problems with access to market information, and institutional problems supporting MSMEs. The digital transformation of business makes entrepreneurs develop and use innovative technologies and business models to gain competitive advantage, at the same time reviewing the costs incurred, benefits and associated threats. This research method uses a qualitative research approach to content analysis. The results show that the FnB (Ramen Master Indonesia) businesshas a great opportunity to gain competitive advantage by using digital transformation, innovative digital business strategies that are based on advanced IT solutions, and that comply with SDGs No. 9.In order to reach all levels of the population in Indonesia, especially generation Z, the FnB business needs to utilize digital promotions and collaborate with content creator.